تمهيدات البحث اللّساني العربي ومؤشراته في كتابي علم اللّغة وفقه اللّغة لعلي عبد الواحد وافي - مهدي, خميسي; حليم, رشيد (جامعة الوادي - University of Eloued, 2020)
تلّقى كثير من اللّسانيين العرب المفاهيم اللّسانيات الغربية حين درسوا في جامعاتها، فأثروا المكتبة العربية بمؤلفات لسانيّة مهمّة؛ منهم علي عبد الواحد وافي بكتابيه؛ علم اللّغة وفقه اللّغة جمع فيهما بين متطلبات التراث اللّغوي العربي ومخصبات الدرس اللّساني الحديث. وفي هذا المضمار تعود مقالتنا إلى مقاربة معرفيّة لبيان المؤشرات اللسانيّة الحديثة في الكتابين المذكورين سابقا، منهجا و محتوى. وتهدف دراستنا هذه إلى التنقيب عن حفريات الدرس اللّساني العربي الحديث من خلال هذين المؤلفين اللّغويين الشهيرين لعبد الواحد وافي. وكيفية تلقيه للمفاهيم اللّسانيّة الحديثة. Many of the Arab linguists received the concepts of Western linguistics when they studied in its universities. Therefore, they enriched the Arab library with the important linguistic writing. Ali Abdul Wafi, was among them with his two books; Linguistics and the Jurisprudence of Language in which he gathered some of the Arab linguistic heritage and the influences of the modern linguistic lesson. In this regard, our article refers to a cognitive approach to show the modern linguistic indicators in the two books mentioned above concerning methodology and content. Our study aims at prospecting the excavation of the modern Arab linguistic lesson through the two famius linguistic writings of Abdul Wafi and how he received modern linguistic concepts.
مقال
Keywords: علم اللّغة ، فقه اللّغة ، الكتابات اللّسانيات، التراث اللّغوي